2007
DOI: 10.1037/1099-9809.13.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Traditions and alcohol use: A mixed-methods analysis.

Abstract: An integrative mixed-methods analysis examined traditional beliefs as associated with beliefs about self-care during pregnancy and with alcohol abstinence among young adult women from two rural U.S.-Mexico border communities. Quantitative (measured scale) variables and qualitative thematic variables generated from open-ended responses served as within-time predictors of these health-related outcomes. A weaker belief that life is better in big cities was associated with stronger self-care beliefs during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…Some authors have suggested mixed qualitative-quantitative methods would better capture acculturation’s multifaceted effect on health (Castro et al, 2010a; Castro & Coe, 2007; Edwards & Lopez, 2006; Kagawa Singer et al, 2016; Sussner et al, 2008); however, these methods are incompatible with the conventional biomedical research paradigm. Better options include the use of bi-dimensional instruments analyzed as two continuous predictive variables, or administering a questionnaire and categorizing individuals based on threshold scores or as naturally-occurring groups based on cluster analysis.…”
Section: Operationalization Of Acculturationmentioning
confidence: 99%
“…Some authors have suggested mixed qualitative-quantitative methods would better capture acculturation’s multifaceted effect on health (Castro et al, 2010a; Castro & Coe, 2007; Edwards & Lopez, 2006; Kagawa Singer et al, 2016; Sussner et al, 2008); however, these methods are incompatible with the conventional biomedical research paradigm. Better options include the use of bi-dimensional instruments analyzed as two continuous predictive variables, or administering a questionnaire and categorizing individuals based on threshold scores or as naturally-occurring groups based on cluster analysis.…”
Section: Operationalization Of Acculturationmentioning
confidence: 99%
“…Hispanics who endorse traditional Hispanic and Mexican cultural values have been found to endorse more conventional attitudes toward gender roles, as contrasted with Hispanics who hold the more modern cultural values prevalent within mainstream U.S. culture (Castro, Stein, & Bentler, 2009; Kulis, Marsiglia, & Nagoshi, 2010). These conventional gender values are particularly evident among Mexican and Mexican American parents and tend to erode with increasing acculturation toward the more egalitarian gender role values of the dominant U.S. culture (Castro & Coe, 2007). The conventional belief that girls are more vulnerable and in greater need of protection (Archer & Lloyd, 2002) may prompt Hispanic parents to provide greater supervision of girls than boys, which in turn would be expected to increase the effect of parenting practices for girls compared with boys.…”
Section: Introdutionmentioning
confidence: 99%
“…We identified and labeled thematic categories by conducting open coding (Strauss and Corbin 1990), discovering and naming emergent categories. We matched these categories with quantitative measures in the PSID, converting qualitative thematic categories into numeric thematic variables (Castro and Coe 2007), and using proxies where we were unable to locate an equivalent variable. The results of the quantitative analyses helped inform the magnitude and significance of the effect of different factors on wealth mobility over time.…”
Section: Integrative Mixed Methods (Imm) Analysismentioning
confidence: 99%